Arthroscopic Osseous Bankart Repair in the Treatment of Recurrent Anterior Glenohumeral Instability - Sugaya, Hiroyuki (JBJS Essent Surg Tech, 2016)
INTRODUCTION: Anterior glenohumeral instability associated with an anterior-inferior fracture of the glenoid (osseous Bankart lesion) can be treated successfully with arthroscopic, rather than open, surgical repair, or fixation of the osseous fragment. INDICATIONS & CONTRAINDICATIONS: STEP 1: PATIENT POSITIONING: Place the patient in the beach-chair position and examine both shoulders for laxity after induction of general anesthesia with an interscalene block. STEP 2: PORTAL PLACEMENT: Create a standard posterior viewing portal and anterior and anterosuperior working portals. STEP 3: MOBILIZATION: Separate the displaced osseous fragment associated with the labroligamentous complex from the glenoid neck and mobilize the labroligamentous complex together with the fragment up to the 7 o’clock or 7:30 position (in a right shoulder). STEP 4: INFERIOR LABRUM REPAIR: Perform an inferior labrum repair by inserting 2 suture anchors at the anteroinferior part of the glenoid face. STEP 5: OSSEOUS FRAGMENT FIXATION: Fix the osseous fragment by passing the sutures either through or around the fragment with use of a bone penetrator, or Bone Stitcher, while stabilizing the labrum and fragment with a large grasper. STEP 6: AUGMENTATION PROCEDURES: Rotator interval closure, done with the arm in >60° of external rotation, is the most frequently performed augmentation procedure. RESULTS: A consecutive series of 46 patients with an osseous Bankart lesion who demonstrated >15% glenoid bone loss underwent osseous Bankart repair, which was performed regardless of the fragment size, between January 2005 and December 2006(1). PITFALLS & CHALLENGES: